2020
DOI: 10.1108/cr-01-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the connection between SMEs’ competitiveness and cash flow generation: an empirical analysis from Hungary

Abstract: Purpose The purpose of this paper is to interconnect the firm level competitive performance (competitiveness) to the financial performance of the firms. The goal is to give evidence on how successful small- and medium-sized enterprises (SMEs) use their financial performance to support their competitive performance. Design/methodology/approach Competitiveness is interpreted and measured through the resource-based view theory on a wide range of competitiveness measurements with a sample size of 639 SMEs. Finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 73 publications
1
11
0
2
Order By: Relevance
“…In the private sector, higher competitiveness is based on returns that are built on cost structures. When a company’s financial position is sufficiently stable, it can transfer resources to long-term strategies (Markus and Rideg, 2021). This study could compare educational institutes’ strategic decisions with cases of community social capital where managers are restrained from making opportunistic resource adjustment decisions and from acting unethically (Hartlieb et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the private sector, higher competitiveness is based on returns that are built on cost structures. When a company’s financial position is sufficiently stable, it can transfer resources to long-term strategies (Markus and Rideg, 2021). This study could compare educational institutes’ strategic decisions with cases of community social capital where managers are restrained from making opportunistic resource adjustment decisions and from acting unethically (Hartlieb et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Through empirical study, Karadag (2018) showed that FP is positively associated with competitiveness in small- and medium-sized companies in Turkey. Markus and Rideg (2021) argued that the direction of causality between competitiveness and FP is an open problem. Based on an empirical study sample from Hungary, they investigated the interconnection between the firm-level competitive performance (competitiveness) and the FP of the firms.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Aset berwujud merupakan bentuk lain dari pengeluaran modal yang bisa menaikkan nilai perusahaan. Investasi pada aset berwujud dipercaya dapat meningkatkan kekayaan pemegang saham (Markus & Rideg, 2020). Adanya kebutuhan investasi dan sumber pendanaan terbatas sering kali membuat perusahaan memilih antara berinvestasi pada aset berwujud atau inovasi melalui kegiatan R&D. Namun, perusahaan juga bisa melakukan sinergi antara aset berwujud dengan R&D seperti pada teori RBV.…”
Section: Kajian Pustaka 21unclassified